1997
DOI: 10.1148/radiology.203.1.9122378
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous hemangioma of the liver: pathologic correlation with dynamic CT findings.

Abstract: Dynamic enhancement patterns of cavernous hemangiomas are related to the collective size of their constituent vascular spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
62
1
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(68 citation statements)
references
References 0 publications
3
62
1
2
Order By: Relevance
“…This result differed from that on enhanced CT. 27,30 It is well known that hemangiomas show various types of enhancement in contrast-enhanced CT and MR imaging, and the possible correlation of the dynamic enhancement pattern of hepatic hemangiomas with the collective size of its constituent vascular spaces has been reported. [31][32][33] The vascular spaces of hemangiomas with diffuse enhancement are relatively small compared to those without diffuse enhancement. 33 Hanafusa's group 4 reported the isoattenuation compared to the surrounding liver parenchyma of approximately half the number of hemangiomas with diffuse enhancement during the portal venous phase on dynamic CT, a pattern also known as high flow hemangioma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result differed from that on enhanced CT. 27,30 It is well known that hemangiomas show various types of enhancement in contrast-enhanced CT and MR imaging, and the possible correlation of the dynamic enhancement pattern of hepatic hemangiomas with the collective size of its constituent vascular spaces has been reported. [31][32][33] The vascular spaces of hemangiomas with diffuse enhancement are relatively small compared to those without diffuse enhancement. 33 Hanafusa's group 4 reported the isoattenuation compared to the surrounding liver parenchyma of approximately half the number of hemangiomas with diffuse enhancement during the portal venous phase on dynamic CT, a pattern also known as high flow hemangioma.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] The vascular spaces of hemangiomas with diffuse enhancement are relatively small compared to those without diffuse enhancement. 33 Hanafusa's group 4 reported the isoattenuation compared to the surrounding liver parenchyma of approximately half the number of hemangiomas with diffuse enhancement during the portal venous phase on dynamic CT, a pattern also known as high flow hemangioma. Doo and colleagues 17 have reported that hemangiomas with diffuse enhancement during the arterial phase show the pseudo washout sign on Gd-EOB-DTPA-enhanced MR imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Therefore, hemangiomas should be included in the differential diagnoses of small hypoattenuating lesions as well as hypervascular lesions. CEUS, which has the advantage of real-time dynamic assessment, could be of help in characterizing such lesions.…”
Section: Discussionmentioning
confidence: 99%
“…It is composed of dilated vascular spaces lined by a single layer of endothelial cells and separated by connective tissue stroma (6,7). A definite diagnosis could be made by demonstrating the typical US, CT, and MRI findings (1).…”
Section: Discussionmentioning
confidence: 99%